Targeting Chemokine—Glycosaminoglycan Interactions to Inhibit Inflammation - Crijns, Helena; Vanheule, Vincent; Proost, Paul (Frontiers in Immunology, 2020)
Leukocyte migration into tissues depends on the activity of chemokines that form concentration gradients to guide leukocytes to a specific site. Interaction of chemokines with their specific G protein-coupled receptors (GPCRs) on leukocytes induces leukocyte adhesion to the endothelial cells, followed by extravasation of the leukocytes and subsequent directed migration along the chemotactic gradient. Interaction of chemokines with glycosaminoglycans (GAGs) is crucial for extravasation in vivo. Chemokines need to interact with GAGs on endothelial cells and in the extracellular matrix in tissues in order to be presented on the endothelium of blood vessels and to create a concentration gradient. Local chemokine retention establishes a chemokine gradient and prevents diffusion and degradation. During the last two decades, research aiming at reducing chemokine activity mainly focused on the identification of inhibitors of the interaction between chemokines and their cognate GPCRs. This approach only resulted in limited success. However, an alternative strategy, targeting chemokine-GAG interactions, may be a promising approach to inhibit chemokine activity and inflammation. On this line, proteins derived from viruses and parasites that bind chemokines or GAGs may have potential to interfere with chemokine-GAG interactions. Alternatively, chemokine mimetics, including truncated chemokines and mutant chemokines, can compete with chemokines for binding to GAGs. Such truncated or mutated chemokines are characterized by a strong binding affinity for GAGs and abrogated binding to their chemokine receptors. Finally, Spiegelmers that mask the GAG-binding site on chemokines, thereby preventing chemokine-GAG interactions, were developed. In this review, the importance of GAGs for chemokine activity in vivo and strategies that could be employed to target chemokine-GAG interactions will be discussed in the context of inflammation.